Differences in ball possessions, contacts with the ball and contact index of the medal winners on the World Championship 2 - Dosic, N. (Sports Science and Health, 2014)
Research attention has been focused on the recording of ball possession. contact with the ball and contact index in the game of medal winners on the World Championship 2010 . Expected due to the placement of the teams that there are no statistically significant differences in the observed characteristics of the football game . There were observed a total of 21 matches . Based on the results obtained by statistical analysis of the data collected using the Kruskal Wallis test can be concluded that there are significant differences in the representation of ball possession (p=0.005) and by contact with the ball (p=0.005),. but in contact index (p=0,129) were not statistically significant differences observed in the game of the observed national teams . Testing of differences between pairs of teams Mann Whitney test showed that between the teams of Spain and the Netherlands, there was no statistically significant difference in all three variables (p <0.05). and between the national teams of the Netherlands and Germany, there were no statistically significant differences ( p > 0.05) . Between teams of Spain and Germany were found statistically significant differences in ball possession and ball contact.